Design and construction of a website-based librarian application system in Bali - Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Kajian Informasi dan Perpustakaan, 2024)
This study focuses on the development of a web-based application system related to the functional positions of librarians in Bali. This web-based application is designed as a one-stop service to provide essential functional position information for librarians. The primary research question asked is how to design and construct a web-based librarian application system in Bali. The objective of this study is to design, develop, and evaluate a system that supports librarians in managing their activities and credit scores. The development method used is the linear sequential (waterfall) method, which includes the stages of analysis, design, coding, implementation, testing, and maintenance. This system features a user interface with functions such as Home, Activity Details, Forms, and a List of Librarians, enabling librarians to manage various activities organized into categories of Expert Librarians and Skilled Librarians. Each activity comprises a menu for librarian type, education, library management, services, librarian system development, professional development, and task support, which are further broken down into sub-activities according to their categories. Application testing was carried out using the Black Box Testing method to ensure that all functions operated according to user needs. This system was implemented as a web-based application using PHP and MySQL databases, allowing librarians to access it online. The implementation results show that this application has run well and is able to meet the needs of librarians in managing their functional positions efficiently, simplifying the credit score submission process, and enhancing accuracy and efficiency in reporting.